Promising roles of erythropoietin and lymphotoxin alpha in critical illness: A pilot study in critically ill children - Seham A. EL Sherbini; Aliaa A. Ali; Sally Kamal; Huda Marzouk; Laila Rashed (SpringerOpen, 2018)
Background: Several studies proved the anti-inflammatory role of erythropoietin. Little is known about the anti-inflammatory role of lymphotoxin alpha (LT-α). This study was designed to investigate the patterns of erythropoietin (EPO) and LT-α levels in children with acute critical illness. Patients and methods: Thirty-two critically ill children were prospectively subjected to serial estimation of EPO and LT-α levels, during the first 10 days of admission to one of the pediatric intensive care unit of Cairo University. Thirteen healthy children served as control. Results: Serial EPO and LT-α measurements showed significant increases over time early in their critical illness (P < 0.001, respectively). Both cytokines showed significant increases in survivors (P < 0.001, respectively). Kaplan Meier survival analysis revealed a significant increase in mortality with LT-α levels below 108.7 pg/ml, (P < 0.01) on admission. However, EPO did not show any significant difference between survivors and non-survivors. For both LT-α and EPO, levels at day 1 showed a significant decrease in septic patients. EPO levels were significantly elevated on day 1 of admission in non-anemic [mean hemoglobin level (11.8 ± 0.9) g/dL, mean EPO level (110.85 ± 44.5) mIU/ml] compared with anemic patients [mean hemoglobin level (9.3 ± 1.3) g/dL, mean EPO level (69.84 ± 30.763) mIU/ml], 95% CI [13.896-68.112], P < (0.01). Conclusions: Both EPO and LT-α showed significant increment in critically ill children especially in survivors. Our data strongly suggest that, LT-α may have an anti-inflammatory role in children with acute critical illness.